Catalytic behavior of Zn(II) and Co(II) molypdates - Palacio, Luz Amparo; Saldarriaga, Carlos; Lombardo, Eduardo (Revista Facultad de Ingeniería Universidad de Antioquia, 2003)
Isotypic molybdates of Zn(Il) and Co(II) were hydro thermally prepared and the solid products characterized by XRD, TGA, AA, SEM, CHN analysis and N2 adsorption. The materials are layered type and exhibit structures formed by Zn and Co octahedrons and molybdenum tetrahedrons with one vertex unconnected which protrudes into the interlayer space. The catalytic behavior was tested by means of the reaction of cyclohexene hydroxylation with hydrogen peroxide. ZnMo shows high selectivity to 2-cyclohexene-1-ol while CoMo shows lower activity than the blank.